Association of plastid lipid metabolism with the activation of systemic acquired resistance in Arabidopsis thaliana - Krothapalli, Kartikeya (Kansas State University, 2008)
Localized inoculation of a plant with an avirulent pathogen results in the activation of systemic acquired resistance (SAR), a defense mechanism that confers enhanced resistance against a variety of pathogens. The activation of SAR requires the translocation of an unknown signal from the pathogen-inoculated organ to the other organs where defenses are primed to respond faster in response to a future attack by a pathogen. Previous studies with the Arabidopsis thaliana dir1 (defective in induced resistance1) and sfd1 (suppressor of fatty acid desaturase deficiency1) mutants implicated a role for plant lipids in the activation of SAR. DIR1 encodes a putative lipid transfer protein and SFD1 encodes a dihydroxyacetone phosphate (DHAP) reductase involved in plastid glycerolipid metabolism. To further evaluate the role of DHAP reductases and plastid lipids in SAR, the involvement of two additional putative DHAP reductase encoding genes (AtGPDHp and AtGPDHc) and the SFD2 gene, which like SFD1 is involved in plastid glycerolipid metabolism, in SAR was evaluated. Only SFD2 was found to be essential for SAR. Although the lipid profile of the sfd2 mutant was similar to that of the fad5 (fatty acid desaturase 5) mutant, sfd2 is not allelic with fad5 and does not influence FAD5 expression. The SFD2 gene was mapped to an 85 kilo basepairs (kb) region on the third chromosome of Arabidopsis. The lipid composition defect of the sfd2 mutant was partially complemented by two independent recombinant bacterial artificial chromosomes (BACs) that contained genomic DNA spanning the wild type SFD2 locus. The role of plastid synthesized glycerolipids in the activation of SAR was further evaluated by characterizing SAR in additional Arabidopsis mutants that were deficient in plastid lipid metabolism. The requirement of MGD1 (MONOGALACTOSYLDIACYLGLYCEROL SYNTHASE 1), DGD1 (DIGALACTOSYL-DIACYLGLYCEROL SYNTHASE 1) and FAD7 (FATTY ACID DESATURASE 7) genes in SAR, confirmed the essential role of plastid glycerolipids, presumably a galactolipid-dependent factor, in signaling associated with the SAR.
Keywords: Plant molecular biology; Plant defense signaling; Biology, Genetics (0369); Biology, Molecular (0307)